Repellents for Dispersing Ham Mites - Strassburg, Meghan; Strassburg, Melissa; Phillips, Thomas (My University, 2017)
Mites can be a major pest in our foods—especially ham and cheese. (US Fed News Service) Currently, there is a huge interest for reducing our impact on the ozone layer, so researchers are looking at ways to prevent pests in our meats in place of fumigating with ozone-depleting methyl bromide. (Targeted News Service) In the past, researchers at K-State have found that propylene glycol can keep mites off of hams (Abbar, et al. 2016). Although there have been a couple of tests on what deters these mites from meats, we wanted to see if spraying the surface area surrounding these foods would deter them as well. So, we investigated what solutions would repel mites the most. It seemed as if rosemary repelled the mites most. Use of natural repellents like Rosemary can represent safe and effective alternatives for pest management.